Influence of employee loyalty and employee satisfaction on maintaining human resources in commercial service firms - Thu, Nguyen Van; Lan, Nguyen Ngoc; Lan, Vu Thi; Tri, Nguyen Van; Dan, To Xuan (Edelweiss Applied Science and Technology, 2025)
Vietnam’s Labor Code (2019, effective from January 1, 2021) establishes fundamental rights and obligations to protect employees and stabilize labor relations, thereby helping enterprises retain their workforce. Retaining human resources plays a key role in ensuring the stability and sustainable development of a business. It helps optimize work performance, minimize costs and risks related to personnel changes, and build a positive and cohesive working environment. The purpose of this study was to investigate the factors affecting the maintenance of human resources (MHR) in commercial service firms in Hanoi City, including employee loyalty (EL) and employee satisfaction (ES). We employed both qualitative and quantitative research methods. With a sample of 288 employees, the results of this research indicate two factors affecting the maintenance of human resources (MHR) in commercial service firms: employee loyalty (EL) and employee satisfaction (ES). Based on the findings, several recommendations are proposed to enhance the retention of human resources through improving employee loyalty and satisfaction. This, in turn, contributes to improving the quality of human resources in commercial service firms in Hanoi. This study also serves as a useful reference for firms and human resource researchers.